MOTIF REMAJA DESA DANAU SIJABUT KECAMATAN AIR BATU DALAM MENGGUNAKAN YOUTUBE USTAZ HANAN ATTAKI - Rubino Rubino; Tengku Walisyah; Siti Rahmadani Lubis (Universitas Negeri Medan, 2022)
Abstract : Youth Motives in Lake Sijabut Village, Air Batu Dalam District Using Ustaz Hanan Attaki's Youtube. The purpose of the study was to find out the motives of teenagers in Danau Sijabut Village, Air Batu District, using Ustaz Hanan Attaki's youtube. The subject of this research is the youth of Lake Sijabut Village who subscribes to Ustaz Hanan Attaki's youtube, teenagers aged 18-22 years, teenagers who actively use youtube social media. This type of research is field research using a descriptive qualitative approach and using a scientific approach, namely communication science. The technique used in collecting data in this study, using unstructured interview techniques. The results of this study can be concluded that the motives of teenagers in Danau Sijabut Village, Air Batu District, in using Ustaz Hanan's youtube basically boils down to the motive of fulfilling information and knowledge about good morals, from previously not understanding to understanding the existence of moral knowledge conveyed on Ustaz's youtube media Hanan Attaki, then also the fulfillment of personal motives (self), and the fulfillment of integrity motives and social interactions related to adolescent morals in Danau Sijabut Village, Air Batu District.